Microfluidic pumping by micromolar salt concentrations. Issue 7 (27th January 2017) - Niu, Ran; Kreissl, Patrick; Brown, Aidan T.; Rempfer, Georg; Botin, Denis; Holm, Christian; Palberg, Thomas; de Graaf, Joost
Abstract : We show that an ion-exchange resin can achieve strong microfluidic pumping over a long range using micromolar salt concentrations. Abstract : An ion-exchange-resin-based microfluidic pump is introduced that utilizes trace amounts of ions to generate fluid flows. We show experimentally that our pump operates in almost deionized water for periods exceeding 24 h and induces fluid flows of μm s −1 over hundreds of μm. This flow displays a far-field, power-law decay which is characteristic of two-dimensional (2D) flow when the system is strongly confined and of three-dimensional (3D) flow when it is not. Using theory and numerical calculations we demonstrate that our observations are consistent with electroosmotic pumping driven by μmol L −1 ion concentrations in the sample cell that serve as 'fuel' to the pump. Our study thus reveals that trace amounts of charge carriers can produce surprisingly strong fluid flows; an insight that should benefit the design of a new class of microfluidic pumps that operate at very low fuel concentrations.